World Health Organization life‐skills training is efficacious in reducing youth self‐report scores in primary school going children in Kenya. Issue 5 (2nd October 2018) - Ndetei, David M.; Mutiso, Victoria; Gitonga, Isaiah; Agudile, Emeka; Tele, Albert; Birech, Lilian; Musyimi, Christine; McKenzie, Kwame
Abstract : Aim: Documented evidence shows that training in life skills for school going children improves their physical and mental health status. Although Kenya has a curriculum and a policy for life‐skills training in schools, these have not been implemented because lack of local evidence for efficacy. Therefore, the objective of this study was to determine the efficacy and effectiveness of the life‐skill training curriculum for primary schools developed by the Ministry of Education, Kenya. Methods: We randomly selected 23 schools from two randomly selected sub‐counties representing urban/peri‐urban and rural contexts in Kenya. We collected baseline socio‐demographic characteristics and administered the locally validated youth self‐report (YSR) for 11 to 18 years old at baseline and 9 months post‐intervention. We used the Ministry of Education validated curriculum for life‐skills training for upper primary school as the intervention immediately after the baseline. Results: The World Health Organization life‐skills training is efficacious in reducing YSR scores in primary school going children in Kenya. We found that socio‐demographic characteristics were predictors for mental health and that there were significant positive improvements in internalizing and externalizing YSR symptoms and syndromes in both sites. The improvement was over 40% and therefore unlikely to be attributable to placebo effect or natural recovery without intervention. However, attention problems worsened more so in rural sites and particularly in girls. Conclusions: Life‐skills training is efficacious in improving mental health in school going children in the Kenyan context. However, it is not effective in attention problems which seem to be cognitive in nature.